2007
DOI: 10.1088/0031-9155/52/10/019
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resolution of 2D ionization chamber arrays for IMRT dose verification: single-detector size and sampling step width

Abstract: The spatial resolution of 2D detector arrays equipped with ionization chambers or diodes, used for the dose verification of IMRT treatment plans, is limited by the size of the single detector and the centre-to-centre distance between the detectors. Optimization criteria with regard to these parameters have been developed by combining concepts of dosimetry and pattern analysis. The 2D-ARRAY Type 10024 (PTW-Freiburg, Germany), single-chamber cross section 5 x 5 mm(2), centre-to-centre distance between chambers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 14 publications
5
99
0
2
Order By: Relevance
“…Strictly, Mobius3D‐ and COMPASS‐calculated values in planar analysis should be convolved with the detector response function and then compared to MatriXX measurements (47) . This problem, described as a limitation of the present study, is not observed in measurement‐based dose reconstruction performed by COMPASS because the system inherently applies this correction.…”
Section: Discussionmentioning
confidence: 93%
“…Strictly, Mobius3D‐ and COMPASS‐calculated values in planar analysis should be convolved with the detector response function and then compared to MatriXX measurements (47) . This problem, described as a limitation of the present study, is not observed in measurement‐based dose reconstruction performed by COMPASS because the system inherently applies this correction.…”
Section: Discussionmentioning
confidence: 93%
“…The White Paper states: “Due to the highly irregular nature and limited resolution of the energy fluence matrix, deviations between calculated and measured dose in the Delta 4 detector positions are more frequent in the IMRT case, … Deviations are primarily localized to regions of the rapid dose changes, indicating distances to agreement less than the pixel size, i. e. <6mm.” It is clear that when the penumbra of individual segments is not represented with sufficient resolution, the superposition of many segments in a modulated beam would lead to rather inaccurate calculations. This is effectively equivalent to calculating modulated beams with a 6×6mm2 pixel size, while it is well established in the literature that segmented beam calculations require 2.5 mm voxel grid resolution to faithfully reproduce encountered gradients 28 , 29 , 30 . This explains poor dosimetric agreement for VMAT plans found in Table 2 and 4, 5, 6.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used dose distribution measurement devices currently available are film 5 , 6 (radiochromic), arrays 7 , 8 (both ion chamber and diodes), and EPIDs. Film has a high resolution, but its use is very time‐consuming; it needs time before scanning, the scanning itself, and a calibration process.…”
Section: Introductionmentioning
confidence: 99%